Democracy as a Way of Life: Critical Reflections on a Deweyan Theme (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This article aims to critically assess John Dewey’s ideal of “democracy as a way of life”, an evocative though elusive moral and political ideal linked to both his communal notion of democracy and his reformist view of liberalism. Beyond the school, where citizenship education begins, Dewey claims that individuals learn democratic habits when they associate and participate in political activities, which are not solely confined to political institutions. Exploring Dewey’s democratic theory invites a twofold account. It takes to contextualize Dewey’s views in light of the political debates of his time, in particular the interwar debates on the crisis of liberalism and democracy. And it takes to examine his democratic thought in terms of educational theory and policy. Both aspects integrate into the argument.